Kesalahan Siswa Sekolah Menengah Pertama dalam Menyelesaikan Soal Matematika Tipe Pisa - Jihan Della Safegi; Hapizah Hapizah; Cecil Hiltrimartin; Made Sukaryawan; Kodri Madang; Ketang Wiyono; Yenny Anwar (Pendidikan Matematika Universitas Muhammadiyah Bangka Belitung, 2021)
This study aimed to determine student errors and the factors that caused students to make mistakes in solving PISA-type math problems. Error analysis was carried out based on Newman's analysis through tests and interviews. This research was conducted in one of the junior high schools in the Province of the Bangka Belitung Islands, involving 26 students. Subjects were selected based on a purposive sampling technique with three considerations: academic ability, teacher recommendations, and student willingness. This study used the descriptive qualitative method. The PISA math test questions tested consisted of change and relationship, space and shape, quantity and uncertainty, and data content. The results showed that reading errors were 40.21%, comprehension errors were 41.86%, transformation errors were 87.29%, process skill error is 90.26%, and the answer writing error is 88.46%. While uncertain and data is the content with the most significant error percentage, which is 82.31%. In general, errors were caused by students who cannot relate PISA questions to the material they usually study, and students were not accustomed to working on PISA questions.